Phenolic Content of Blends of Tempranillo with Graciano or Cabernet Sauvignon Wines Produced in Spain - María Monagas; Verónica Núñez; Begoña Bartolomé; Carmen Gómez-Cordovés (Food Technology and Biotechnology, 2006)
The effect of Graciano (GRA, Spanish valuable variety of limited production in Mediterranean countries) vs. Cabernet Sauvignon (CS, world-wide known French variety) on the phenolic content [total polyphenols (TP), total anthocyanins (TA), catechins (CAT) and proanthocyanidins (PRO)] of Tempranillo wines (TEM-BASE, a largely cultivated Spanish variety) was studied in blends prepared with 25 and 10 % of each variety after 4, 6, 9, 16.5 and 23 months of bottle ageing. Significant differences among wines (blends and base wine) according to the »blend« factor were observed for CAT and TA. Besides, although the evolution trend during wine ageing of different families of phenolic compounds studied was similar in the blends and base wine, different blends presented a faster anthocyanin disappearance kinetics than the base wine, probably due to their higher CAT content, which may favour the progress of certain anthocyanin condensation reactions during ageing in the bottle. This effect was slightly more pronounced in the TEM-GRA blends than in the TEM-CS ones. A further study of the phenolic composition of the monovarietal wines used for blending, as well as of the grapes (skins and seeds) from which these wines were elaborated, revealed that the blending effect on CAT could be associated with higher concentration of these compounds in Graciano and Cabernet Sauvignon grape seeds in comparison with Tempranillo. Finally, the findings of this work scientifically confirm that, in terms of the phenolic content, Graciano wines possess properties similar to Cabernet Sauvignon for blending with Tempranillo.